A Proposed Settlement and Distribution Structure for Music Royalties in Korea and Their Artificial Intelligence-Based Applications - Youngmin Kim; Donghwan Kim; Sunho Park; Yonghwa Kim; Jisoo Hong; Sunghee Hong; Jinsoo Jeong; Byounghyo Lee; Hyeonchan Oh (Applied Sciences, 2023)
Digital music is one of the most important commodities on the market due to music royalty distribution in Korea. As the music market has been transformed into a digital music market by means such as downloading and streaming, the distribution of music royalties via online service providers (OSPs) has become a highly important issue for music rights holders. Currently, one of the most important issues in music royalty distribution in Korea is the unfair distribution of royalties due to the indiscriminate repeat streaming of digital music. To prevent this, music consumption log data from several OSPs were collected via a day-based system; however, there was a limit on the identification of detailed information on the use of music in its current state. This paper analyzes the structural problems and limitations related to the settlement of music royalties and provides a structure in which there can be transparent settlement and distribution between users and rights holders as an institutional measure. We also propose various AI (artificial intelligence)-based applications using music consumption log data. The proposed system will hopefully be used for public purposes.